Risk and Return Evaluation: A Modern Portfolio Theory Approach on Bina Puri Berhad and Ahmad Zaki Resources Berhad Stocks - Fauziyah, Nur; Athia Nur Kamilah; Chetrine Alya Rinaima (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study analyzes investment strategies based on Modern Portfolio Theory (MPT) using a case study of two Malaysian construction companies, Bina Puri Holdings Bhd and Ahmad Zaki Resources Berhad (AZRB). The study evaluates the risk and return of both companies' stocks using variables such as average closing price, average return rate, variance, and standard deviation. The results show that Bina Puri Berhad has a higher average return (36.43%) compared to AZRB (11.23%), but it also comes with higher risk. The correlation between the two stocks was found to be weakly positive (0.1759), indicating potential diversification benefits within a portfolio. By applying MPT principles, the study identifies the optimal portfolio combination that minimizes risk while maximizing returns. The findings highlight the importance of diversification in portfolio management and the relevance of MPT in strategic investment decision-making.